Exercise training attenuates sympathetic activation and oxidative stress in diet-induced obesity - Li, G; Liu, J-Y; Zhang, H-X; Li, Q; Zhang, S-W (Physiological research, 2015)
It is known that excessive sympathetic activity and oxidative stress are enhanced in obesity. This study aimed to clarify whether exercise training (ET) attenuates sympathetic activation and oxidative stress in obesity. The obesity was induced by high-fat diet (HFD) for 12 weeks. Male Sprague-Dawley rats were assigned to four groups: regular diet (RD) plus sedentary (RD-S), RD plus ET (RD-ET), HFD plus sedentary (HFD-S), and HFD plus ET (HFD-ET). The rats in RD-ET and HFD-ET groups were trained on a motorized treadmill for 60 min/day, five days/week for 8 weeks. The sympathetic activity was evaluated by the plasma norepinephrine (NE) level. The superoxide anion, malondialdehyde and F2-isoprostanes levels in serum and muscles were measured to evaluate oxidative stress. The ET prevented the increases in the body weight, arterial pressure and white adipose tissue mass in HFD rats. The NE level in plasma and oxidative stress related parameters got lower in HFD-ET group compared with HFD-S group. We have found decreased mRNA and protein levels of toll-like receptor (TLR)-2 and TLR-4 by ET in HFD rats. These findings suggest that ET may be effective for attenuating sympathetic activation and oxidative stress in diet-induced obesity.
Keywords: výsledek terapie; oxidační stres; Male; Physical Conditioning, Animal; sympatický nervový systém; Obesity; potkani Sprague-Dawley; reaktivní formy kyslíku; terapie cvičením; obezita; kondiční příprava zvířat; Diet, High-Fat; mužské pohlaví; dieta s vysokým obsahem tuků; Body Weight; Treatment Outcome; krysa rodu Rattus; Reactive Oxygen Species; Animals; Sympathetic Nervous System; zvířata; Exercise Therapy; Rats; Oxidative Stress; tělesná hmotnost; Rats, Sprague-Dawley